2016
DOI: 10.1002/mdc3.12321
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Movement Disorders in Neuromyelitis Optica: An Under‐recognized Phenomenon

Abstract: Background: Spinal cord demyelination can cause several movement disorders. Although these abnormal movements could be the presenting symptom of the disease and, at times, the major source of disability, they are often overlooked, mislabeled, or undertreated. The aims of this study were to clearly define and establish common terminology for spinal movement disorders (SMDs) and characterize their full spectrum in patients with neuromyelitis optica (NMO). Methods: We chart reviewed 37 patients with NMO or NMO sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Per our previously reported definition, 6 11 patients (18.3%) had focal paroxysmal dystonia of the upper or lower extremity following a well-defined spinal (8) or brainstem relapse (1). One patient with primary progressive MS had focal dystonia from a right thalamic lesion and in one patient the origin was undetermined.…”
Section: Focal Dystoniamentioning
confidence: 95%
“…Per our previously reported definition, 6 11 patients (18.3%) had focal paroxysmal dystonia of the upper or lower extremity following a well-defined spinal (8) or brainstem relapse (1). One patient with primary progressive MS had focal dystonia from a right thalamic lesion and in one patient the origin was undetermined.…”
Section: Focal Dystoniamentioning
confidence: 95%
“…Several case reports and small series describe PTS in NMOSD ( 18 , 29 , 29 31 , 65 67 , 136 , 141 144 ), but no reports were identified mentioning PTS in MOGAD. Abboud et al reported that all patients with tonic spasms had associated neuropathic pain ( 145 ). PTS and pain occur more frequently in NMOSD than in MS ( 18 , 29 ), and PTS-associated myelitis in AQP4-Ab-positive NMOSD has been described with a specificity of 98.7% compared to MS ( 143 ).…”
Section: Types Of Pain In Nmosd and Mogadmentioning
confidence: 99%
“…Focal spinal cord disease can cause a variety of involuntary movements including tonic spasms, paroxysmal or fixed focal dystonia, spinal myoclonus, spontaneous or triggered clonus, spinal tremor, and secondary restless leg syndrome (RLS) [33][34][35]. Some of these movement disorders, in particular tonic spams and paroxysmal dystonia, are thought to be more common in NMOSD than other demyelinating diseases and they can be painful [36][37][38][39].…”
Section: Tonic Spasms and Other Involuntary Movementsmentioning
confidence: 99%
“…Some of these movement disorders, in particular tonic spams and paroxysmal dystonia, are thought to be more common in NMOSD than other demyelinating diseases and they can be painful [36][37][38][39]. The prevalence of any spinal movement disorder in NMOSD is estimated at 43% while the prevalence rates for tonic spasms in particular range from 22 to 40% depending on the study [33,36,38]. They commonly occur several weeks to months following a spinal attack but they can occasionally be the presenting symptom of a new spinal relapse [33].…”
Section: Tonic Spasms and Other Involuntary Movementsmentioning
confidence: 99%
See 1 more Smart Citation